THE INFLUENCE OF EXCELLENT TEACHERS ON INCREASING THE LEARNING MOTIVATION OF CLASS XI STUDENTS AT MA NW MONTONG BAAN - Nur Hamiyetun (al-Hikmah : Jurnal Studi Islam, 2022)
Excellent teachers have a very big influence on increasing student learning motivation. But the fact that happened at that time, excellent teachers did not optimize themselves as motivators in the learning process. As a result, students experience a decrease in interest in learning. This study aims to determine (1) the role of excellent teachers as motivators (2) learning motivation (3) the effect of the role of excellent teachers as motivators on learning motivation at MA Montong Baan. The research design used is causality with a population of 68 students and a total sample of 16 students. Data were collected using documentation and questionnaire methods, analyzed using quantitative with a descriptive approach. The results showed that (1) Excellent teachers played a good role as a motivator for MA Montong Baan students. This can be shown from the results of the questionnaire with a total score of 4497 ​​in the range of scores of 3905-4288. (2) Good student motivation in MA Montong Baan. This can be shown from the results of the questionnaire with a total score of 4622 in the range of scores of 3905 –4822. (3) The role of excellent teachers as motivators has a positive and significant effect on learning motivation at MA Montong Baan shown > ie 6.570 > 1.989 with p-value < ie 0.000 < 0.05. The value of R Square is 0.350. This shows that the contribution of the role of the excellent teacher as a motivator (X) on learning motivation (Y) is 35%.